2020
DOI: 10.1007/s40119-020-00206-2
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Testing for D-Dimer in the Diagnosis of Venous Thromboembolism in Primary Care: A Narrative Review

Abstract: Venous thromboembolism (VTE) is regarded as a significant cause of mortality and disability, affecting 1–2 per 1000 people annually, presenting with a relatively wide range of symptoms, which can pose a diagnostic challenge. Historically, people in whom VTE is suspected will have been taken to hospital for diagnosis and treatment; however, a high proportion of patients are found not to have VTE. Concerns have been expressed about potential delays in treatment, with the risk of additional morbidity and disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The latest NICE guidance already recommends using quantitative POC testing within such settings, as part of a defined diagnostic pathway, which limits unnecessary referrals [8]. Previous studies using qualitative POC D-dimer assays have demonstrated substantial benefits in terms of reducing unnecessary referrals for imaging without increasing the number of patients with undiagnosed VTE [12]. A greater disparity between D-dimer measurements at concentrations [ 1000 lg/l were observed between the LumiraDx D-Dimer Test and the bioMe ´rieux VIDAS D-Dimer Exclusion II immunoassay (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latest NICE guidance already recommends using quantitative POC testing within such settings, as part of a defined diagnostic pathway, which limits unnecessary referrals [8]. Previous studies using qualitative POC D-dimer assays have demonstrated substantial benefits in terms of reducing unnecessary referrals for imaging without increasing the number of patients with undiagnosed VTE [12]. A greater disparity between D-dimer measurements at concentrations [ 1000 lg/l were observed between the LumiraDx D-Dimer Test and the bioMe ´rieux VIDAS D-Dimer Exclusion II immunoassay (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The NICE recommendation for POC testing for D-dimer in the primary care setting has the potential to reduce the number of unnecessary hospital referrals, thereby improving patient experience on the diagnosis pathway and relieving pressure on healthcare resources [12,13]. Indeed, prospective management studies have shown that even qualitative POC Ddimer tests can rule out a large proportion of patients who do not need a referral (up to 49%) [12,14,15], with low false-negative rates (1.4-2%) [12]. Moreover, the sensitivity and specificity of a combined clinical score and qualitative POC D-dimer test were comparable to the laboratory-based quantitative test [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Price et al, (2021), there has been a substantial decrease in health care expenses implemented by hospitals. It has facilitated the establishment of a long-term relationship with patients and hospital administration in Middle Eastern countries.…”
Section: Healthcare System's Reaction To Price-innovation Schemesmentioning
confidence: 99%
“…Lastly, promising new diagnostic opportunities are emerging, such as easy-to-use point-of-care (POC) D-dimer tests, which enable performing a D-dimer test, preceded or not by a CDR, in a one-stop visit at the GP’s office (Ellis et al., 2021 ; Heerink et al., 2020 ; Price et al., 2021 ). In this way, the time delay that comes with referring the patient to the laboratory for a D-dimer test can be eliminated, potentially lowering the threshold for using a CDR.…”
Section: Decision Rules Within Primary Carementioning
confidence: 99%